2009 IEEE International Conference on Computational Photography (ICCP) 2009
DOI: 10.1109/iccphot.2009.5559010
|View full text |Cite
|
Sign up to set email alerts
|

Light field superresolution

Abstract: Light field cameras have been recently shown to be very effective in applications such as digital refocusing and 3D reconstruction. In a single snapshot these cameras provide a sample of the light field of a scene by trading off spatial resolution with angular resolution. Current methods produce images at a resolution that is much lower than that of traditional imaging devices. However, by explicitly modeling the image formation process and incorporating priors such as Lambertianity and texture statistics, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(111 citation statements)
references
References 25 publications
4
107
0
Order By: Relevance
“…High resolution images can be obtained via professional cameras, but these cameras are usually costly. The spatial resolution can be enhanced computationally: e.g., Wilburn et al [84] captured high resolution images using a large camera array, while Bishop et al [119] raised image resolution by introducing prior constraints, and Landolt et al [120] attained the same goal by introducing mechanical vibrations (named jittering) to the image sensor; Wang et al [121] and Ben-Ezra [122] designed large format cameras for high resolution image capture. One newly proposed work is the giga-pixel imaging proposed by Cossairt et al [123], who designed a compact architecture composed of a ball lens shared by several small planar sensors, and a post-capture image processing stage; one example image captured by their prototypes is shown in Figure 4.…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…High resolution images can be obtained via professional cameras, but these cameras are usually costly. The spatial resolution can be enhanced computationally: e.g., Wilburn et al [84] captured high resolution images using a large camera array, while Bishop et al [119] raised image resolution by introducing prior constraints, and Landolt et al [120] attained the same goal by introducing mechanical vibrations (named jittering) to the image sensor; Wang et al [121] and Ben-Ezra [122] designed large format cameras for high resolution image capture. One newly proposed work is the giga-pixel imaging proposed by Cossairt et al [123], who designed a compact architecture composed of a ball lens shared by several small planar sensors, and a post-capture image processing stage; one example image captured by their prototypes is shown in Figure 4.…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…One technique is to obtain multiple viewpoints by capturing multiple coded images [8,13,22] or by capturing a single image by using a plenoptic camera [9,6,23,24]. These methods however, exploit multiple images or require a more costly optical design (e.g., a calibrated microlens array).…”
Section: Depth-invariant Blurmentioning
confidence: 99%
“…Perhaps one of the most remarkable results is to have shown that it is possible to extend the depth of field of a camera by modifying the camera optical response [1,2,3,4,5,6,7]. Moreover, techniques based on applying a mask at the lens aperture have demonstrated the ability to recover a coarse depth of the scene [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several LF super-resolution algorithms have been proposed to recover the lost resolution [12,4]. The Plenoptic2.0 camera [12] recovers the lost resolution by placing the microlens array at a different location compared to the original design [24].…”
Section: Related Workmentioning
confidence: 99%
“…Thus, it is clear that there exists a resolution barrier ( Figure 1) for capturing high resolution LF video. Recently, a series of approaches such as Plenoptic 2.0 camera [12] and LF super-resolution techniques [4] have begun breaking this resolution barrier. Simulated scene with moving butterfly and beetle and static grass.…”
Section: Introductionmentioning
confidence: 99%